A multicriteria approach to choose the best renewable refrigeration system for food preservation. (July 2020) - Rech, Sergio; Finco, Elisa; Lazzaretto, Andrea
Abstract: Food spoilage represents an urgent issue in tropical developing countries because of the lack of correctly refrigerated post-harvest storage, transportation and distribution facilities. This paper searches for the best choice of configuration and design parameters of food refrigeration systems integrated with renewable conversion units in tropical areas using a multicriteria approach (energetic, exergetic and economic). Fourty-four technically feasible integrated configurations are identified for three preservation temperatures of the food (8, 2 and −20 °C). Each configuration is simulated from the energetic, exergetic and economic point of view during one year of operation using detailed design and off-design models. A thermal storage or the connection with the electric grid is considered in the integrated configurations fuelled by solar energy to guarantee a continuous operation. Results show that the PV-powered flash-intercooled compression system is the most efficient integrated configuration for each food storage temperature (annual average COP in the range 2.3–5.7) but it represents the most economically viable option only for the highest food preservation temperature. At lower temperatures, the single-effect absorption cycle coupled with a bagasse-fired boiler shows lower costs because of the very low price of bagasse in tropical countries. On the other hand, all options including the half-effect absorption cycle result to be the less promising in terms of both COP and costs. Highlights: Flesh-intercooled systems show the highest COP (2.2–4.5) for Tfood = 8, 2, -20 °C. Best annual COPs (0.9–2.1) are obtained by compression systems + PV-panels. Best average annual η e x are of the order of 10% (compression) and 5% (absorption). Compression systems show the lowest total annual costs ( 575 to 935 € / k W c o o l i n g ). Selling the electricity from absorption + biogas-ICE options leads to economic gains.